Cardiac Mesenchymal Cells Cultured at Physiologic Oxygen Tension Have Superior Therapeutic Efficacy in Heart Failure Caused by Myocardial Infarction - Bolli, Robi A. R.; Arshia, Asma; Hassan, Syed A.; Dasari, Chandrashekhar; Nong, Yibing; Guo, Yiru; Tomlin, Alex A.; Li, Qianhong (Frontiers in Cell and Developmental Biology, 2021)
Stem/progenitor cells are usually cultured at atmospheric O2 tension (21%); however, since physiologic O2 tension in the heart is ∼5%, using 21% O2 may cause oxidative stress and toxicity. Cardiac mesenchymal cells (CMCs), a newly discovered and promising type of progenitor cells, are effective in improving left ventricle (LV) function after myocardial infarction (MI). We have previously shown that, compared with 21% O2, culture at 5% O2 increases CMC proliferation, telomerase activity, telomere length, and resistance to severe hypoxia in vitro. However, it is unknown whether these beneficial effects of 5% O2in vitro translate into greater therapeutic efficacy in vivo in the treatment of heart failure. Thus, murine CMCs were cultured at 21% or 5% O2. Mice with heart failure caused by a 60-min coronary occlusion followed by 30 days of reperfusion received vehicle, 21% or 5% O2 CMCs via echocardiography-guided intraventricular injection. After 35 days, the improvement in LV ejection fraction effected by 5% O2 CMCs was > 3 times greater than that afforded by 21% O2 CMCs (5.2 vs. 1.5 units, P < 0.01). Hemodynamic studies (Millar catheter) yielded similar results both for load-dependent (LV dP/dt) and load-independent (end-systolic elastance) indices. Thus, two independent approaches (echo and hemodynamics) demonstrated the therapeutic superiority of 5% O2 CMCs. Further, 5% O2 CMCs, but not 21% O2 CMCs, significantly decreased scar size, increased viable myocardium, reduced LV hypertrophy and dilatation, and limited myocardial fibrosis both in the risk and non-infarcted regions. Taken together, these results show, for the first time, that culturing CMCs at physiologic (5%) O2 tension provides superior therapeutic efficacy in promoting cardiac repair in vivo. This concept may enhance the therapeutic potential of CMCs. Further, culture at 5% O2 enables greater numbers of cells to be produced in a shorter time, thereby reducing costs and effort and limiting cell senescence. Thus, the present study has potentially vast implications for the field of cell therapy.